2019
DOI: 10.3389/fvets.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Wharton's Jelly Derived Mesenchymal Stem Cells Application on a Large Chronic Skin Wound in a 6-Month-Old Filly

Abstract: A complex feedback of growth factors, secreted by a variety of cell types, is responsible for the mediation of skin healing. Despite the recent advances in wound healing management, this fails up to 50% and skin wounds can still be considered one of the main causes of morbidity, both in human and veterinary medicine. Regenerative medicine, involving mesenchymal stromal cells (MSCs), is nowadays a promising solution for skin wound healing. Indeed, MSCs are involved in the modulation of the inflammatory local re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…Further, WJMSCs isolated from fetal tissue have several unique beneficial properties including easy isolation, higher proliferation capacity, and potentially strong immunomodulatory effects [9]. Previous studies have reported the beneficial effects of WJMSCs on large full-thickness cutaneous wounds in animal models [10,11]. However, it is believed that poor engraftment, retention, and survival of the transplanted stem cells are the important barriers affecting their therapeutic efficiency on wound regeneration [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Further, WJMSCs isolated from fetal tissue have several unique beneficial properties including easy isolation, higher proliferation capacity, and potentially strong immunomodulatory effects [9]. Previous studies have reported the beneficial effects of WJMSCs on large full-thickness cutaneous wounds in animal models [10,11]. However, it is believed that poor engraftment, retention, and survival of the transplanted stem cells are the important barriers affecting their therapeutic efficiency on wound regeneration [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Human amnion mesenchymal stem cells (hAMSCs) are obtained by surgery from human amniotic tissue and are now often used as an alternative resource for stem cell therapy [13]. According to research reports, stem cells exert repair effects through paracrine signaling and affect cell proliferation and migration through the release of bioactive factors [14].…”
Section: Discussionmentioning
confidence: 99%
“…Complete healing of the non-healing skin wound was also observed in a filly after repeated local application of heterologous Wharton/s Jelly derived MSC with the use of carboxymethylcellulose gel. The wound healed completely in 5 days (249).…”
Section: Skin Diseases and Wound Healingmentioning
confidence: 93%